Payment for Environmental Services and Polder Sustainable Management in the Context for Poverty Reduction in Semarang - Edi Santoso; Shudarto P. Hadi; Y. Warella (Jurnal Studi Pemerintahan, 2013)
Environmental issues are externalities of economic development requires the handling of various instruments in order to be in harmony with the eco[1]nomic development environment. Payment for Environmental Services (PES) is now being developed globally as a market-based instrument that is promising to address the issue of degradation of natural resources and the environment. PES mechanism has to be said that the concept is simple and flexible in a variety of conditions, so that the application was highly variable throughout the world. The main problem lies in whether the Payment for Environmental Services (PES) that is now being developed globally as a market-based instruments are quite capable of dealing with poverty and degradation of natural resources and the environment. Refer to research finding shows that Tawang Polder has significant direct and indirect value for society. About 50% household stated that they accept PES and 20% who reject the PES. Even PES is quiet potential in reducing poverty in these areas. Even in the society level such as huge support in Polder systems, social capital and local wisdom, the system management of polder should be designed appropriately and have to increase the level of participation in decision making. Another factor is also important is polder institution which has to be design clearly and transparent based on performance standart. The last factor is politic capital should be aware of democratization.